Nordic contributions in IS research : 6th Scandinavian Conference on Information Systems, SCIS 2015, Oulu, Finland, August 9-12, 2015, Proceedings /: 6th Scandinavian Conference on Information Systems, SCIS 2015, Oulu, Finland, August 9-12, 2015, Proceedings. (2015) - Unknown
No abstract available